A Three-Dimensional Finite Element Model for Biomechanical Analysis of the Hip - Guang-Xing Chen; Liu Yang; Kai Li; Rui He; Bin Yang; Yan Zhan; Zhi-Jun Wang; Bing-Nin Yu; Zhe Jian (Cell Biochemistry and Biophysics, 2013)

Molecular phylogeny and biogeography of lac insects (Hemiptera: Kerriidae) inferred from nuclear and mitochondrial gene sequences - Hang Chen; Xiaoming Chen; Ying Feng; Hui Yang; Rui He; Wenfeng Zhang; Zixiang Yang (Molecular Biology Reports, 2013)

Development of an immunochromatographic strip test for the rapid detection of okadaic acid in shellfish sample - Leqin Hu; Junxiu Liu; Qing Wang; Yang Zhang; Rui Jia; Chuner Cai; Weining Wu; Steven-Feng Chen; Peimin He (Journal of Applied Phycology, 2013)

Determination of oxidized scytonemin in Nostoc commune Vauch cultured on different conditions by high performance liquid chromatography coupled with triple quadrupole mass spectrometry - Juanjuan Chen; Lijuan Zhao; Jilin Xu; Rui Yang; Shan He; Xiaojun Yan (Journal of Applied Phycology, 2013)

Treatment with exogenous hydrogen sulfide attenuates hyperoxia-induced acute lung injury in mice - Huai-Dong Li; Zhao-Rui Zhang; Qing-Xiang Zhang; Zhi-Chu Qin; Deng-Ming He; Jin-Song Chen (European Journal of Applied Physiology, 2013)

Selection and characterization of colorectal cancer cell-specific peptides - Han Wang; Caixia Ma; Rui Li; Yonge Guo; Yakun He; Xiaojing Wang; Yiwen Chen; Yingchun Hou (Biotechnology Letters, 2013)

WHAMM is required for meiotic spindle migration and asymmetric cytokinesis in mouse oocytes - Xin Huang; Lu Ding; Rui Pan; Peng-Fei Ma; Pan-Pan Cheng; Chun-Hui Zhang; Yu-Ting Shen; Lin Xu; Yu Liu; Xiao-Qin He; Zhong-Quan Qi; Hai-Long Wang (Histochemistry and Cell Biology, 2013)

Changes of net primary productivity in China during recent 11 years detected using an ecological model driven by MODIS data - Yibo Liu; Weimin Ju; Honglin He; Shaoqiang Wang; Rui Sun; Yuandong Zhang (Frontiers of Earth Science, 2013)

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .

The roles of ADIPOQ genetic variations in cancer risk: evidence from published studies - Yeqiong Xu; Bangshun He; Yuqin Pan; Ling Gu; Zhenlin Nie; Liping Chen; Rui Li; Tianyi Gao; Shukui Wang (Molecular Biology Reports, 2013)

Optimization of biotransformation from phytosterol to androstenedione by a mutant Mycobacterium neoaurum ZJUVN-08 - Xiao-yan Zhang; Yong Peng; Zhong-rui Su; Qi-he Chen; Hui Ruan; Guo-qing He (Journal of Zhejiang University-SCIENCE B, 2013)

Screening level ecological risk assessment for synthetic musks in surface water of Lake Taihu, China - Guang-Hui Guo; Feng-Chang Wu; Hong-Ping He; Rui-Qing Zhang; Hui-Xian Li (Stochastic Environmental Research and Risk Assessment, 2013)